answersLogoWhite

0


Best Answer

a2+b2+c2=x2+y2+z2

divide each side by 2

(a2+b2+c2)/2=(x2+y2+z2)/2

a+b+c=x+y+z

User Avatar

Wiki User

โˆ™ 2010-05-28 00:21:36
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides
๐Ÿ““
See all Study Guides
โœ๏ธ
Create a Study Guide

Add your answer:

Earn +20 pts
Q: If a plus b plus c equals x plus y plus z then prove a2 plus b2 plus c2 equals x2 plus y2 plus z2?
Write your answer...
Submit
Related questions

If a2 plus b2 equals c2 then c2 equals b2 equals?

a2


Why is the Pythagorean therm a2 plus b2 equals c2 not a plus b equals c?

l a2 b2 is c2!!Its completely norma


If a2 plus b2 equals c2 then the triangle is?

a right triangle


A2 plus b2 equals c2 is an example of?

Pythagorean Theorem


How do you calucate a2 plus b2?

a2+2a2b+2ab2+b2


What are the lengths of and A plus B in a right triangle if C equals 8?

A2 + B2 = C2 If C=8, then A2 + B2 = 64


What is the algebraic formula for a2 plus b2 equals c2?

You just typed it.


If a2 plus b2 plus c2 - ab - bc - ca equals 0 then prove a equals b equals c?

a2 + b2 + c2 - ab - bc - ca = 0 => 2a2 + 2b2 + 2c2 - 2ab - 2bc - 2ca = 0 Rearranging, a2 - 2ab + b2 + b2 - 2bc + c2 + c2 - 2ca + a2 = 0 => (a2 - 2ab + b2) + (b2 - 2bc + c2) + (c2 - 2ca + a2) = 0 or (a - b)2 + (b - c)2 + (c - a)2 = 0 so a - b = 0, b - c = 0 and c - a = 0 (since each square is >=0) that is, a = b = c


Who introduced a2 plus b2 equals c2?

Pythagoras' theorem for a right angle triangle.


Factor A2 plus 4a plus 4 - b2?

a2 - 4a + 4


CosA equals a2 plus c2 minus b2 by 2ac what is this formula?

This is known as the Cosine Rule.


Are there numbers with the property that the sum of their squares equals the square of their sum?

Yes, as long as either number is 0. a2 + b2 = (a+b)2 a2 + b2 = a2 + 2ab + b2 0 = 2ab


Is a squared plus b squared the same as a plus b squared?

No. If you expand (a + b)2 you get a2 + 2ab + b2. This is not equal to a2 + b2


Math inventor of a2 plus b2 equals c2?

Pythagoras. That's why it's called the Pythagorean Theorem.


How do you simplify the square root of a squared plus b squared?

sqrt(a2 + b2) can't be simplified. Neither can (a2 + b2) .


Chords lyre of lupang hinirang with lyrics?

Lupang hinirang intro:g f# a2 g d/a2 b2 c2 b2 a2 b2 g/g f# a2 g d/ a2 b2 c2 b2 a2 g/g f# a2 g d/a2 b2 c2 b2 a2 b2 g/ g f# a2 g d/a2 b2 c2 b2 a2 g/ refrain:g f# g a2 a2 d d a2 a2 d d/b2 c2 b2 e2 d2/ g f# g a2 a2 d d a2 a2 d d/b2 c2 b2 a2 b2 a2 g/(2x) g f# g c2 c2 d2 d2 e2 d2 c2 d2 e2/f2 e2 d2 e2 c2 d2 b2 b2 c2r/(2x)


What theoremcontains the formula c2 equals a2 plus b2?

Pythagoras' theorem. This is telling us that, for a right angled triangle, the square of the hypotenuse (c2) is equal to the sum of the square of the other two sides (a2 + b2).


How do you solve a2 plus c2 equals b2 and a equals 10 and your c is 30?

All you need to do is substitute the given values of a and c into the equation, then solve for c: a2 + c2 = b2 102 + 302 = b2 100 + 900 = b2 b2 = 1000 b = √1000 b = 10√10


What is Pythagoras famous quotes?

a2+b2=c2 a squared plus b squared equals c squared


How do you solve a to the 3rd power plus b to the 3rd power divided by a plus b?

(a3 + b3)/(a + b) = (a + b)*(a2 - ab + b2)/(a + b) = (a2 - ab + b2)


Who is the first person to prove the geometric theory a2 b2c2?

If you mean a2+b2 = c2 then it's Pythagoras' theorem


The formula c2 equals a2 plus b2 tells the relationship between the lengths of the sides in a right triangle what is it known as?

The Theorem of Pythagoras.


What is the formula of a2 plus b2 plus c2?

It is a*a + b*b + c*c


Who first proposed the therom a2 plus b2 equals c2?

Pythagoras, the Greek Mathematician. The Pythagorean theorem (P Theorem) ~ a2 + b2 = c2 Also used to find the hypotenuse of certain triangles.


Can you simplify the square root of a2 plus b2?

Cannot be simplified